Thoracic Outlet Syndrome Part I: Systematic Review of the Literature and Consensus on Anatomy, Diagnosis, and Classification of Thoracic Outlet Syndrome by the European Association of Neurosurgical Societies' Section of Peripheral Nerve Surgery. Issue 6 (25th June 2022) - Dengler, Nora Franziska; Ferraresi, Stefano; Rochkind, Shimon; Denisova, Natalia; Garozzo, Debora; Heinen, Christian; Alimehmeti, Ridvan; Capone, Crescenzo; Barone, Damiano Giuseppe; Zdunczyk, Anna; Pedro, Maria Teresa; Antoniadis, Gregor; et al.
Abstract : BACKGROUND: Although numerous articles have been published not only on the classification of thoracic outlet syndrome (TOS) but also on diagnostic standards, timing, and type of surgical intervention, there still remains some controversy because of the lack of level 1 evidence. So far, attempts to generate uniform reporting standards have not yielded conclusive results. OBJECTIVE: To systematically review the body of evidence and reach a consensus among neurosurgeons experienced in TOS regarding anatomy, diagnosis, and classification. METHODS: A systematic literature search on PubMed/MEDLINE was performed on February 13, 2021, yielding 2853 results. Abstracts were screened and classified. Recommendations were developed in a meeting held online on February 10, 2021, and refined according to the Delphi consensus method. RESULTS: Six randomized controlled trials (on surgical, conservative, and injection therapies), 4 "guideline" articles (on imaging and reporting standards), 5 observational studies (on diagnostics, hierarchic designs of physiotherapy vs surgery, and quality of life outcomes), and 6 meta-analyses were identified. The European Association of Neurosurgical Societies' section of peripheral nerve surgery established 18 statements regarding anatomy, diagnosis, and classification of TOS with agreement levels of 98.4 % (±3.0). CONCLUSION: Because of the lack of level 1 evidence, consensus statements on anatomy, diagnosis, and classification of TOS from experts of the section of peripheral nerve surgery of the European Association of Neurosurgical Societies were developed with the Delphi method. Further work on reporting standards, prospective data collections, therapy, and long-term outcome is necessary.